Hydrogel films based on sodium alginate modified with octane-1-amine: enhanced pore formation and potential applications in drug delivery systems - A. V. Sikach; V. V. Konovalova; I. S. Kolesnyk (Хімія, фізика та технологія поверхні, 2024)
The use of wound dressings is gaining more and more popularity, especially in the field of tactical and military medicine. Developing wound dressings capable of facilitating wound treatment and reducing healing time is one of the challenges of modern science. So, sodium alginate (Alg) is a good candidate for the development of wound dressings due to its bio- and hemocompatibility and biodegradability. However, Alg has its shortcomings, which can be dispatched by modification.